KONSEP DASAR PSIKOANALISIS: PROSES DAN TUJUAN KONSELING PSIKOANALISIS - Kartika Ayu Nurjanah; Margareta Widyasari; Aulia Kholifatul Jannah; Siska Kusumaningrum; Allesheva Arka Fyandha Almachumi; Muh Nasril Refarelsyah Putra; Radithya Ganendra; Bakhrudin All Habsy; Shopyan Jepri Kurniawan (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
Psychoanalysis is a classical approach in psychology that emphasizes the role of unconscious dynamics in shaping individual behavior. This article aims to examine the basic concepts of psychoanalysis as well as to outline the processes and goals of psychoanalytic counseling. Psychological problems from this perspective are understood as the result of unresolved intrapsychic conflicts, particularly those rooted in childhood experiences. The counseling process is carried out through an in-depth exploration of the client's experiences and internal dynamics, utilizing techniques such as free association, dream interpretation, and transference analysis. The main goal of psychoanalytic counseling is to help individuals gain insight, strengthen ego functions, and be able to manage internal conflicts more adaptively. This approach provides an important contribution to understanding humans more comprehensively, not only from the aspect of observable behavior but also from unconscious mental processes.